Odpowiedzi

2010-02-18T18:56:05+01:00
1)
[3(x-y)+4x=8
[3(x-5y)=5-9y

[3x-3y+4x=8
[3x-15y=5-9y

[7x-3y=8
[3x-15y+9y=5

[7x-3y=8
[3x-6y=5

[7x=8+3y/:7
[3x-6y=5

[x=8/7 + 3/7y
[3x-6y=5

[x=8/7+3/7y
[3(8/7+3/7y)-6y=5

[x=8/7+3/7y
[24/7+9/7y-6y=5

[x=8/7+3/7y
[24/7-4 5/7y=5

[x=8/7+3/7y
[-4 5/7y=5-24/7

[x=8/7+3/7y
[-4 5/7y= 1 4/7 /: (-4 5/7)

[x=8/7+ 3/7y
[y=11<kreska> 7 : (-33<kreska>7)

[x=8/7 + 3/7y
[y= 11<kreska> 7 * (-7<kreska> 33)

[x=8/7+3/7y
[y= -1/3

[x=8/7+3/7y
[y=-1/3

[x=8/7 + 3/7 * (-1/3)
[y=-1/3

[x=8/7+(-1/7)
[y=-1/3

[x=1
y=-1/3



2)
[3(2x-1)+ 4(y-2) = 9
[2(5x -1) + 3y = 5(3x+y) +2

[6x-3+4y-8=9
[10x-2+3y=15x+5y+2

[6x+4y=9+8+3
[10x+3y-5y-15x=2+2

[6x+4y=20
[-5x-2y=4

[6x+4y=20
[-2y=4+5x/: (-2)

[6x+4y=20
[y=-2-5/2x

[6x+4(-2-5/2x)=20
[y=-2-5/2x

[6x-8-10x=20
[y=-2-5/2x

[-4x=20+8/:(-4)
[y=-2-5/2x

[x=-7
[y=-2+35/2

[x=-7
[y=34,5